On the structure and ecology of the micro-fauna in the Central Amazonian forest stream 'Igarapé da Cachoeira' - Walker, Ilse (Hydrobiologia, 1985)
A method was developed to sample the microfauna in open stream water and to observe its food habits over long periods in the laboratory. Evaluation of the material leads to the following conclusions: 1. The microfauna is primarily associated with submerged leaf litter. Its density in the open water is a function of water current and hence, of rainfall, 2. A considerable quantity of living and detritus-biomass is swept down-stream with each heavy rain, 3. The foodweb starts essentially with decomposing fungi and detritus, and to a much lesser extent with algae and bacteria. Protozoa and Rhabdocoela are an insignificant input into the foodweb of higher invertebrates, but their role for maintenance of water quality may be important. Prey of fishes and shrimps depends primarily on 'primary input', i.e. on detritus, fungi and to some extent on algae and bacteria. The role of biomass transport from forest streams into larger rivers is discussed in relation to the fauna of the periodically inundated forest (igapó). © 1985 Dr W. Junk Publishers.